Highly Energy-efficient Conversion of Lignite to H2 and Power. (May 2017) - Aziz, Muhammad
Abstract: A state-of-the art integrated system for co-production of H2 and power from lignite with high energy efficiency is proposed. The system is developed based on the principles of enhanced process integration technology. It consists of coal drying, gasification, chemical looping, power generation, and hydrogenation. Enhanced process integration incorporates effectively both heat circulation and process integration technologies, therefore exergy destruction throughout the integrated system can be minimized. Iron oxides are used as oxygen carrier and circulated in chemical looping module consisting of three continuous processes: reduction, oxidation and combustion. A liquid organic H2 carrier of toluene-methylcyclohexane is adopted to store the produced H2 . The effect of fluidization velocity in drying and pressure in chemical looping are evaluated in terms of power generation, H2 production and total energy efficiencies. The proposed integrated system shows very high efficiencies which are about 12, 72, and 84%, respectively.